2021
DOI: 10.11606/s1518-8787.2021055003225
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and mental health of pregnant women in Ceará, Brazil

Abstract: OBJECTIVE To assess the perceptions of pregnant women about COVID-19 and the prevalence of common mental disorders during the implemented social distancing period. METHODS This was an observational, cross-sectional study using digital media, of pregnant women exposed to social distancing due to the COVID-19 pandemic, in Fortaleza, Ceará, Northeastern Brazil. Common mental disorders were estimated using the modified Self-Report Questionnaire-20 (SRQ-20) scale, and the feelings towards COVID-19 were assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
1
17
0
3
Order By: Relevance
“…As expected, in the current study, mothers' CMD symptoms were higher in the pandemic group. This is consistent with previous studies regarding the possible effects of the COVID-19 pandemic on mental health that found higher levels of depressive, stress, and anxiety symptoms in parents and pregnant women after the pandemic started both in Brazil (Machado et al, 2021) and worldwide (American Psychological Association, 2020; Lebel et al, 2020;Vescovi et al, 2021;Wu et al, 2020;Yuan et al, 2020). Besides COVID-related worries, the observed increase in mothers' CMD symptoms could be attributed to challenges faced by them, such as household and parenting demands added to health and economic concerns.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, in the current study, mothers' CMD symptoms were higher in the pandemic group. This is consistent with previous studies regarding the possible effects of the COVID-19 pandemic on mental health that found higher levels of depressive, stress, and anxiety symptoms in parents and pregnant women after the pandemic started both in Brazil (Machado et al, 2021) and worldwide (American Psychological Association, 2020; Lebel et al, 2020;Vescovi et al, 2021;Wu et al, 2020;Yuan et al, 2020). Besides COVID-related worries, the observed increase in mothers' CMD symptoms could be attributed to challenges faced by them, such as household and parenting demands added to health and economic concerns.…”
Section: Discussionsupporting
confidence: 93%
“…For the Iracema-COVID survey, the sample size ( n = 352) was calculated to detect a prevalence of 46% of maternal CMD (Machado et al, 2021), with a margin of error of 5%, and a 95% confidence interval (CI). Out of 4,840 mothers who gave birth in July and August 2020, 3,567 were eligible for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Women who gave birth in private hospitals were deemed ineligible due to not having their contact information available in public records. The sample was designed to be representative of Fortaleza at the administrative district level (SR ( Secretaria Regional )) and to detect a prevalence of 45.7% of maternal common mental disorders (CMDs), 10 with a margin of error of 5% and 95% confidence interval (n=352). Of the 3567 mothers who gave birth in July and August 2020, 352 were sampled for the study ( figure 1 ).…”
Section: Cohort Descriptionmentioning
confidence: 99%